A Critique of Indian National Water Policies: Some Major Issues and Insights - Kumari, Shobha; Bilas, Ram (National Geographical Journal of India, 2022)
Indian national water policies are generally criticized for not having any convergence with the expectations and requirements of different water-resource-regions of the country. Structural allocation-regulation mechanisms have disproportionately dominated this policy regime for generations. Still, a vast stretch of the country is in urgent need of non-structural solutions and use of conjunctive resource management principles. Officially, these policies are claiming to shift their focus from supply ends towards demand adjustments. However, the existing patterns of water demand of the population across the country have never been comprehensively assessed. So, this stated policy goal of demand adjustment does not have any proper base. This paper has included a number of vital issues in the said contexts in order to explain the gap between policy formulations and geographical realities of the nation. A thematic overview of the problem has been prepared with the help of a number of secondary data sources.